PWE-097 Pharmacological treatments for primary sclerosing cholangitis: a network meta-analysis. (22nd June 2015) - Gurusamy, K; Saffioti, F; Toon, C; Davidson, B; Tsochatzis, E; Thorburn, D
Abstract : Introduction: The optimal pharmaceutical treatment of primary sclerosing cholangitis (PSC) remains controversial. We performed a systematic review and network meta-analysis of different pharmacological interventions for the treatment of patients with PSC. Method: We included randomised controlled trials (RCTs) of various pharmacological interventions compared with each other or with placebo in patients with PSC. We conducted network meta-analyses following the National Institute for Health and Care Excellence Decision Support Unit guidance to compare multiple interventions simultaneously for each of the primary (mortality, adverse events, health-related quality of life (HRQoL)) and secondary outcomes (decompensated cirrhosis, liver transplantation, malignancies) and only included trials in which participants could receive any of the interventions being assessed (transitivity assumption). We conducted a Bayesian network meta-analysis and calculated the odds ratios (OR), rate ratios, or hazard ratios with 95% credible intervals or Bayesian confidence intervals (CrI) for assessing the effect of treatment. We used three different non-informative priors and ensured that the results converged prior to calculation of posterior probabilities for Bayesian network meta-analysis. Results: We included 22 RCTs on different treatment regimens for PSC, comprising of 1111 patients. There was no statistically significant difference in the mortality at 1-year, 5-years or at maximal follow-up between any of the treatments and placebo. There was no statistically significant difference in the proportion of patients with any adverse event, serious adverse events, liver decompensation, liver transplant, any malignancy, cholangiocarcinoma, or colorectal cancer at maximal follow-up or in the HRQoL between any of the treatments and placebo. Penicillamine was associated with higher number of total adverse events compared to placebo (rate ratio 1.93; 95% CrI 1.07 to 3.49) and to low-dose ursodeoxycholic acid (rate ratio 2.38; 95% CrI 1.02 to 5.56). There was no statistically significant difference in the total number of serious adverse events between any of the treatments and placebo. Conclusion: None of the current therapies for primary sclerosing cholangitis are effective. Disclosure of interest: K. Gurusamy: None Declared, F. Saffioti: None Declared, C. Toon: None Declared, B. Davidson: None Declared, E. Tsochatzis: None Declared, D. Thorburn Grant/Research Support from: Boston Scientific to fund a clinical research fellow.